On‐chip magnetophoretic capture in a model of malaria‐infected red blood cells. Issue 4 (25th January 2022) - Giacometti, Marco; Monticelli, Marco; Piola, Marco; Milesi, Francesca; Coppadoro, Lorenzo P.; Giuliani, Enrico; Jacchetti, Emanuela; Raimondi, Manuela T.; Ferrari, Giorgio; Antinori, Spinello; Fiore, Gianfranco B.; Bertacco, Riccardo
Abstract: The search for new rapid diagnostic tests for malaria is a priority for developing an efficient strategy to fight this endemic disease, which affects more than 3 billion people worldwide. In this study, we characterize systematically an easy‐to‐operate lab‐on‐chip, designed for the magnetophoretic capture of malaria‐infected red blood cells (RBCs). The method relies on the positive magnetic susceptibility of infected RBCs with respect to blood plasma. A matrix of nickel posts fabricated in a silicon chip placed face down is aimed at attracting infected cells, while healthy cells sediment on a glass slide under the action of gravity. Using a model of infected RBCs, that is, erythrocytes with methemoglobin, we obtained a capture efficiency of about 70% after 10 min in static conditions. By proper agitation, the capture efficiency reached 85% after just 5 min. Sample preparation requires only a 1:10 volume dilution of whole blood, previously treated with heparin, in a phosphate‐buffered solution. Nonspecific attraction of untreated RBCs was not observed in the same time interval. Abstract : An easy‐to‐operate, flow‐less lab‐on‐chip for the magnetophoretic capture of malaria‐infected red blood cells was devised. A matrix of nickel posts fabricated in a silicon chip placed face down attracts infected cells, while healthy cells sediment on a glass slide under the action of gravity. The authors systematically characterized the chip using a model of infected red blood cells.